Examining the Views of Student Teachers on the Meaning of Crafting - Rönkkö, Marja-Leena; Yliverronen, Virpi (Aalto-yliopisto, 2025)
The purpose of the present study is to examine the views of student teachers on the meaning of crafting. It employs a qualitative case study approach and uses essay submissions from a sample of craft student teachers enrolled in a craft-related course. The findings suggest that making crafts plays a significant role in both their personal lives and their academic pursuits. The student teachers perceive craft making as more than a merely recreational activity; rather, it is a means of expressing their creativity, honing their skills, and promoting sustainability. According to the study, crafts as a subject could take on a broader role by engaging students in cultural competence and enhancing their well-being.